Silencing circular RNAPTPN12 promoted the growth of keloid fibroblasts by activating Wnt signaling pathway via targeting microRNA-21-5p. Issue 2 (1st February 2022) - Liu, Fei; Li, Tao; Zhan, Xiaoan
ABSTRACT: Keloid is a skin disease marked by fibroplasia, and fibroblasts viability plays a considerable part in keloid. Our research was devoted to assessing the involvement and mechanism of circPTPN12 in keloid. The level of circPTPN12 and miR-21-5p was estimated by qRT-PCR in keloid tissues and cells. MTT analysis was devoted to evaluating the multiplication of keloid fibroblasts. Additionally, transwell assay was dedicated to verifying cell migration and invasion. Furthermore, keloid fibroblasts apoptosis level was assessed adopting flow cytometry, and the relevancy between miR-21-5p and circPTPN12, miR-21-5p, and SMAD7 was assessed by dual luciferase assay. Similarly, RIP and RNA pull-down assay verified the relevance between genes. Moreover, levels of SMAD7 and proteins concerned in Wnt signaling pathway were appraised by Western blot. The level of circPTPN12 declined in keloid. circPTPN12 knockout could enhance the multiplication, migration, invasion, and decline apoptosis of keloid fibroblasts. Indeed, miR-21-5p could be packed with circPTPN12 sponge, SMAD7 was downstream effect factor of miR-21-5p, and miR-21-5p inhibitors partially reversed the promoting effect of silencing circPTPN12 on keloid formation. Otherwise, the level of SMAD7 was adjusted by circPTPN12 and miR-21-5p. Silencing circPTPN12 targeted miR-21-5p and activated Wnt pathway to accelerate keloid fibroblasts growth. Taken together, silencing circPTPN12 promotes the growth of keloid fibroblasts by activating Wnt pathway targeting miR-21-5p. CircPTPN12 may play a considerable part in keloid formation, which supplies a reference for molecularly targeted therapy keloid. Graphical abstract: uf0001